Volume 1: Aircraft Engine; Marine; Turbomachinery; Microturbines and Small Turbomachinery 1997
DOI: 10.1115/97-gt-469
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Wake-Wake Interactions on Loss Fluctuations of a Downstream Axial Compressor Blade Row

Abstract: The interaction between wakes of an adjacent rotor-stator or stator-rotor blade row pair in an axial turbomachine is known to produce regular spatial variations in both the time-mean and unsteady flow fields in a frame relative to the upstream member of the pair. This paper examines the influence of such changes in the free-stream disturbance field on the viscous losses of a following blade row. Hot-wire measurements are carried out downstream of the outlet stator in a 1.5-stage axial compressor having equal b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…Halstead et al (1995) observed a twofold variation in momentum thickness over a rotor wake passing period at 90% suction surface length for their third stage high pressure compressor stator baseline case (28). For the compressor stator of the present investigation, Walker et al (1997a) reported near wake momentum thickness varying by a factor of about 4 in the peak unsteadiness configuration. Such large perturbations in boundary layer thickness may have important implications for stall inception.…”
Section: Introductionmentioning
confidence: 44%
See 1 more Smart Citation
“…Halstead et al (1995) observed a twofold variation in momentum thickness over a rotor wake passing period at 90% suction surface length for their third stage high pressure compressor stator baseline case (28). For the compressor stator of the present investigation, Walker et al (1997a) reported near wake momentum thickness varying by a factor of about 4 in the peak unsteadiness configuration. Such large perturbations in boundary layer thickness may have important implications for stall inception.…”
Section: Introductionmentioning
confidence: 44%
“…This model neglects turbulence decay during convection downstream, and also possible turbulence production through straining near the stator leading edge. Measurements downstream of the rotor by Walker et al (1997b) showed the random turbulence component to vary only slowly with axial position.…”
Section: Prediction Of Transition Onset -Temporal Variation Freestreamentioning
confidence: 99%
“…In all cases, time resolved HWA data was recorded for one-hundred revolutions of the HP shaft Is worth of data, and post-processed using the techniques described below. For the reduction of the instantaneous data obtained from the hot wire measurements, the following procedure was employed, Walker (1997).…”
Section: Range Of Investigationmentioning
confidence: 99%
“…This has been 2 International Journal of Rotating Machinery done to study vane clocking, the circumferential indexing of adjacent vane rows with similar vane counts. Researchers have shown that vane clocking can impact stage loss and efficiency by changing the amount of interaction the upstream vane wakes have with the downstream vane boundary layer [5][6][7][8]. In this research, clocking is used to isolate the flow field effects associated with the downstream vane potential field.…”
Section: Introductionmentioning
confidence: 99%